(untitled) (Journal of Hama University, 2019)
The objective of this study is to determine the effect of the application of Povidone ointment 10% , compared with the ointment Fusidic acid 2% on healing limbs wounds of the horses. The study is includes (48) horses with limb wounds injury. The limb wounds in horses have been classified according to the period of time that passed on the wounds (recent or old), where the injury proportion of recent wounds(75%), while old wounds with ( 25%) . The horses with limb wounds are divided into two groups, randomly, the ages from two to eighteen years and their weights between (350 and 175) Kg : The first group: (n=24) are treated by using the ointment of Povidone 10% topically on the wounds. The second group: (n=24) are treated by using the ointment of Fusidic acid 2% topically on the wounds. It has been concluded that this study has shown that healing of limb wounds in horses treated by using the ointment of Fusidic acid (2%) was better than using Povidone 10% , in terms of speed of wound contraction , Where the average number of days for healing by Fusidic acid is (±72) and the average number of days of healing by Povidone is (±83),in terms of the constitution of prominent scar and also in terms of the average number of times of eradication of excessive granulation tissue.